2003
DOI: 10.5194/acp-3-1199-2003
|View full text |Cite
|
Sign up to set email alerts
|

A model study of ozone in the eastern Mediterranean free troposphere during MINOS (August 2001)

Abstract: Abstract.A coupled tropospheric chemistry-climate model is used to analyze tropospheric ozone distributions observed during the MINOS campaign in the eastern Mediterranean region (August, 2001). Modeled ozone profiles are generally in good agreement with the observations. Our analysis shows that the atmospheric dynamics in the region are strongly influenced by the occurrence of an upper tropospheric anti-cyclone, associated with the Asian summer monsoon and centered over the Tibetan Plateau. The anti-cyclone a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 24 publications
4
56
0
3
Order By: Relevance
“…Improvements in the specification of the vertical diffusion coefficients were suggested but evaluation was limited due to the lack of measurements of the vertical concentration profiles. Biswas and Rao (2001) report substantial differences between different models adding to uncertainties in ozone simulations and Roelofs et al (2003) suggest that coarse vertical resolution may lead to excessive dispersion. Brandt et al (1998) analysed different vertical dispersion schemes and found that the simplest scheme of high vertical dispersion yielded the best results, suggesting that non-local dispersion is an important factor.…”
Section: Vertical Dispersionmentioning
confidence: 99%
“…Improvements in the specification of the vertical diffusion coefficients were suggested but evaluation was limited due to the lack of measurements of the vertical concentration profiles. Biswas and Rao (2001) report substantial differences between different models adding to uncertainties in ozone simulations and Roelofs et al (2003) suggest that coarse vertical resolution may lead to excessive dispersion. Brandt et al (1998) analysed different vertical dispersion schemes and found that the simplest scheme of high vertical dispersion yielded the best results, suggesting that non-local dispersion is an important factor.…”
Section: Vertical Dispersionmentioning
confidence: 99%
“…Numerous researchers have identified the EM as a "hot spot" of summertime tropospheric ozone (e.g., Stohl et al, 2001;Roelofs et al, 2003;Zbinden et al, 2013;Zanis et al, 2014;Doche et al, 2014;Safieddine et al, 2014). Zbinden et al (2013) derived the climatological profiles and column contents of tropospheric O 3 from the Measurement of Ozone by Airbus in-service Aircraft program (MOZAIC) over the mid-northern latitudes (24 to 50 • N) over the 1994-2009 period.…”
Section: Processes Controlling O 3 Formationmentioning
confidence: 99%
“…Given the observed ratio of SO 4 to total S of 40-90 % in the region (Matvev et al, 2002;Sciare et al, 2003), the annual flux of SO 4 based on field measurements is 0.024-0.054 Tg yr −1 . Rudich et al (2008) used satellite data to estimate the pollution transport toward the EM. MODIS Terraand Aqua-derived estimates of the annual SO 4 flux along the same transect are 0.038 and 0.040 Tg yr −1 , respectively, in the middle of the range obtained from field observations.…”
Section: Particulate Sulfate (So 4 ) Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Hence these disturbances are a mechanism for mixing stratospheric air into the troposphere and for intercontinental transport of pollutants. The latter is widely studied at present through campaigns such as NARE and MINOS, and through model studies (e.g., Fehsenfeld et al [1996] (see also International Global Atmospheric Chemistry project (IGAC), IGACtivities, issue 24, 2001, at http://www.igac.unh.edu), Lelieveld et al [2002], Stohl and Trickl [1999], Jacob et al [1999], Roelofs et al [2003], and Trickl et al [2003]). …”
Section: Introductionmentioning
confidence: 99%